2018
DOI: 10.3390/polym10030310
|View full text |Cite
|
Sign up to set email alerts
|

Reusable Xerogel Containing Quantum Dots with High Fluorescence Retention

Abstract: Although various analytical methods have been established based on quantum dots (QDs), most were conducted in solution, which is inadequate for storage/transportation and rapid analysis. Moreover, the potential environmental problems caused by abandoned QDs cannot be ignored. In this paper, a reusable xerogel containing CdTe with strong emission is established by introducing host–guest interactions between QDs and polymer matrix. This xerogel shows high QDs loading capacity without decrease or redshift in fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
(81 reference statements)
1
6
0
Order By: Relevance
“…Likewise, the second study reports the fabrication of host-guest aerogels containing fluorescently active quantum dots. In the same way that the interaction with CD protects the small molecules from degradation, this study demonstrated the fluorescence-retention potential of quantum dots upon complexation/interaction with β-CD [3].…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Likewise, the second study reports the fabrication of host-guest aerogels containing fluorescently active quantum dots. In the same way that the interaction with CD protects the small molecules from degradation, this study demonstrated the fluorescence-retention potential of quantum dots upon complexation/interaction with β-CD [3].…”
supporting
confidence: 55%
“…By encapsulating oxygen into the cavities of α-CD and α-CD polymers, in vitro cell studies demonstrated a marked reduction in hypoxia-reoxygenation injury, leading to favorable cell growth and lowered cell mortality [4]. Similar to the approach reported by the first two studies [2,3], the fourth study reported the fabrication of a polyrotaxane (PR) containing α-CD and poly [ethylene glycol] containing silver sulfadiazine. When encapsulated in the PR matrix, silver sulfadiazine demonstrated not only superior antibacterial activity against E. coli and S. aureus, but also resistance to light-induced degradation [5].…”
mentioning
confidence: 93%
“…It is well known that β-CD can form stable inclusion complexes with adamantane and its derivatives in an aqueous environment; 32 similarly, Poly-CD can also form the inclusion complex (HEMA-Ad@Poly-CD) with HEMA-Ad. The host− guest interaction between HEMA-Ad and Poly-CD was studied by 2D NOESY spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…2.14. Fe(acac) 3 @SiO 2 @PVA hybrid X-G superparamagnetic nanocomposites In previous decades, nanotechnologies had attained high success in fabrication and characterizing of magnetic nanocomposites with customized properties, capable of being utilized in versatily in as drug/gene delivery, bioseparation, magnetic resonance imaging, hyperthermia and as catalysts in chemical synthesization [20][21][22][23].…”
Section: Fabrication and Properties Of Cork@silica X-g Nanocompositesmentioning
confidence: 99%